Recent Advances in Reconfigurable Electromagnetic Surfaces: Engineering Design, Full-Wave Analysis, and Large-Scale Optimization - Jung, Incheol; Peng, Zhen; Rahmat-Samii, Yahya (Electromagnetic science (Print), 2024)
This paper presents a comprehensive review of recent advances in reconfigurable electromagnetic (EM) surfaces. The discussion is organized around three key aspects of reconfigurable EM surfaces: unit cell engineering design, full-wave numerical analysis, and large-scale optimization techniques. Numerous references are provided to facilitate further exploration of this compelling and timely subject. To address the above three key aspects, we conduct an extensive examination of the design process for metasurfaces in reconfigurable devices. This involves evaluating the design methodology of unit cells, EM simulation techniques tailored for highly complex structures, and innovative optimization methods suitable for scenarios with numerous variables. In scenarios featuring reconfigurability for real-time manipulation of EM waves to meet the requirements of emerging communication environments, the optimization cost function is defined with multiple variables, exhibiting intricate behavior in the design space. Consequently, it necessitates an optimization methodology capable of handling high-dimensional functions without getting trapped in local minima. Moreover, the intricate geometries of metasurface devices preclude analytical solutions, necessitating high-performance full-wave solvers capable of providing highly accurate simulations with minimal computational expense. Key concepts and details pertaining to the aforementioned design stages are presented in a unified manner, along with representative examples.